PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBANTUAN PERMAINAN MONOPOLI UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK SMA - Sari, Sapna Mutiara (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
This research aims to: (1) produce physics learning media assisted by monopoly games that are feasible to use to increase students' interest and learning outcomes and (2) determine the effectiveness and practicality of physics learning media assisted by monopoly games in increasing students' interest and learning outcomes. This research is a development research (RD) with the 4D model consisting of stages (1) define, (2) design, (3) develop, and (4) disseminate. The products developed were in the form of lesson plans, media, learning interest questionnaires and test question instruments. The subjects in this study were students of SMA Negeri 1 Pengasih class XI MIPA 2 as the experimental class and XI MIPA 4 as the control class. The results showed that: (1) the learning media developed is feasible to use in physics learning with a very good category, (2) the learning media developed is effective and practical to be used to increase the interest and learning outcomes of high school class XI students with an effect value. The effect size value for learning outcomes on learning interest is 0.764 which is included in the large category and the effect size value for learning outcomes is 0.527 which is included in the large category.